Gender Differences in the Impact of Worklife on Executives` Psychological Health - Mueller, Marcus (Zielona Góra: Faculty of Economics and Management Press)
This is the first scientific research studying the impact of worklife factors on executives` psychological health by gender. The study has a particular focus on the factors of ?Community? and ?Work-life balance?. Survey data were collected from N=481 senior executives to measure seven worklife factors and psychological health.
Keywords: work; leadership; executives; well-being; życie zawodowe; przywództwo; kierownictwo; dobre samopoczucie